Profile Study of Drug and Supplement Use in COVID-19 January 2022 – December 2022 at the Purworejo Regional Hospital - Ayu Nissa Ainni; Chondrosuro Miyarso; Anwar Sodik; Vinca Elyana Purwanti (Sean Institute, 2023)
Coronavirus 19 or known as COVID-19 is a disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. Treatment for COVID-19 is still in the form of supportive therapy and symptomatic therapy. In addition, the use of drugs is more on the complaints felt by patients and comorbidities. This study aims to look at the profile of drug and supplement use in COVID-19 patients at Hospital X, Purworejo area. This research is included in descriptive research with retrospective data collection. The data for this study consisted of all prescriptions and medical records of COVID-19 patients for the January-December 2022 period who met the inclusion criteria. The results of collecting data on COVID-19 patients who met the inclusion criteria obtained 100 medical record data. The characteristics of COVID-19 patients at Hospital X Purworejo area are dominated by men, in the age group over 65 years, with patients who have a history of comorbid pneumonia, and length of stay of more than 5 days. The results of the treatment profile of COVID-19 patients based on supportive therapy found the most use of antivirals, namely Favipiravir 97 (13.05%), use of antibiotics, namely ceftriaxone 31 (4.18%), use of vitamins 109% (72.97%), use of antihypertensive drugs 49 (6.61%), and based on symptomatic therapy according to frequent symptoms, 51 (6.88%) analgesics and antipyretics were found, 91 mucolytics (12.28%), 69 digestive disorders (9.31%).